Atomic layer deposition of high-k dielectrics on III–V semiconductor surfaces. Issue 4 (December 2016) - Gougousi, Theodosia
Abstract: The goal of this article is to provide an overview of the state of knowledge regarding the Atomic Layer Deposition (ALD) of metal oxides on III–V semiconductor surfaces. An introduction to ALD, the band structure, various defects present on the III–V surface and how they relate to Fermi level pinning are discussed. Surface passivation approaches are examined in detail in conjunction with experimental and computational results. The "interface clean-up" reaction that leads to the formation of a sharp gate oxide/semiconductor interface is related to the surface chemistry and the transport of the surface oxides through the growing dielectric film. Finally, the deposition of metal oxides on semiconductors is discussed in the context of interface quality and some examples of devices using III–V channels and ALD metal oxides are given.